Direct Infection of B Cells by Dengue Virus Modulates B Cell Responses in a Cambodian Pediatric Cohort - Upasani, Vinit; Vo, Hoa Thi My; Auerswald, Heidi; Laurent, Denis; Heng, Sothy; Duong, Veasna; Rodenhuis-Zybert, Izabela A.; Dussart, Philippe; Cantaert, Tineke (Frontiers in Immunology, 2021)
Dengue is an acute viral disease caused by dengue virus (DENV), which is transmitted by Aedes mosquitoes. Symptoms of DENV infection range from inapparent to severe and can be life-threatening. DENV replicates in primary immune cells such as dendritic cells and macrophages, who contribute to dissemination of the virus. Susceptibility of other immune cells such as B cells to direct infection by DENV and their subsequent response to infection is not well defined. In a cohort of 60 Cambodian children, we showed that B cells are susceptible to DENV infection. Moreover, we show that B cells can support viral replication of laboratory adapted and patient-derived DENV strains. B cells were permissive to DENV infection albeit low titres of infectious virions were released in cell supernatants CD300a, a phosphatidylserine receptor, was identified as a potential attachment factor or receptor for entry of DENV into B cells. Inspite of expressing Fcγ-receptors, antibody-mediated enhancement of DENV infection was not observed in B cells in an in vitro model. Direct infection by DENV induced proliferation of B cells in dengue patients in vivo and plasmablast/plasma cell formation in vitro. To summarise, our results show that B cells are susceptible to direct infection by DENV via CD300a and the subsequent B cell responses could contribute to dengue pathogenesis.